AND AGRONOMICAL CHARACTERS ON 18 SELECTED GENOTYPES OF BAMBARA GROUNDNUT (Vigna Subterranea (L.) VERDCOURT) - Ning Fias, Nofita Ayu; Purnamaningsih, Sri Lestari; Kuswanto, Kuswanto (Jurnal Produksi Tanaman, 2015)
In Indonesia, bambara groundnut (Vigna subterranea (L.) Verdcourt) is an unpopular and minor crops, but it has an important role in the food diversification program. Bambara groundnut contains high carbohydrate and protein with relatively low fat. Recently the demand of bambara groundnut began to increase the imbalance between supply and demand is an excellent chance to develop this crop. An effort to increase crop production through plant breeding programs require genetic variability of plant populations. The purpose of this research is to determine variability of morphological and agronomical characters on 18 selected genotypes of bambara groundnut. This research was conducted at the experimental field state on Jatikerto of Agriculture Faculty, University of Brawijaya, Malang. Research began December 2013 until May 2014. The research using a Randomized Complete Block Design (RCBD) with three replications. The materials used 13 local genotypes come from Sumedang, Lamongan, Bangkalan and introduction genotypes from University of Kasetsart Thailand. The result of this research show that there were different variability of morphological character, except characters of pod shape and pigmentation on wings and banner flower. While there were different variability of agronomical characters, except characters of number of leaves. The value of genetic variability coeffisient on all characters were low, while the value of phenotip variability coefficient only in character results was quite high. Keywords: Bambara Groundnut, Variability, Morphological, Agronomical.